“Rete Leonardo” piccole imprese e professionisti in rete: come fare networking per migliorare la competitività - Sacchi, Enrica (Piccola Impresa / Small Business, 2013)
Rete Leonardo is an innovative example of “network contract” ’s (a new legislative instrument promoted by the Italian Governement) application to the service sector. In this case study professionals and small businesses collaborate in order to improve their competitiveness, to increase their knowledge and develop services that could fail to achieve individually. Through the network contract small and medium enterprises try to seize the opportunities offered by the market without losing the benefits related to their special features such as flexibility and knowledge of the local territory.